Challenges for central banks in a changing payments landscape - Anna Iwańczuk-Kaliska (e-Finanse: Financial Internet Quarterly, 2017)
The aim of the paper is to discuss key challenges facing central banks due to evolution of payment systems. The author distinguishes two aspects of the problem. The first one considers the implications of changes in payments for the roles of central banks in national payment systems, namely their role as operators, oversight authorities and catalysts. The second question is how evolution of payment systems influences the nature of central banking. The study is based on the literature review and the analysis and assessment of the information coming from the reports of international institutions. It also uses the results of the author's survey, which was conducted among central banks of eleven countries. The research leads to the conclusion that the challenges for central banks concern among others: monitoring and assessing innovations and new mechanisms of payments, information policy in the area of payments, promotion of standardization and interoperability of systems, effective oversight and operational activities of central banks. The changing payments landscape also requires consideration of long-term implications for monetary policy and central banks' revenues.
Keywords: E58; G21; G23; 330; central banks; payments; banks